Family Altruism and Incentives - Gatti, Roberta (World Bank, Washington, DC, 2014)
The author builds on the altruistic model of the family, to explore the strategic interaction between altruistic parents, and selfish children, when children's efforts are endogenous. If there is uncertainty about the amount of income the children will realize, and if parents have imperfect information, the children have an incentive to exert little effort, and to rely on their parent's altruistically motivated transfers. Because of this, parents face a tradeoff between the insurance that bequests implicitly provide their children, and the disincentive to work prompted by their altruism. The author shows that if parents can credibly commit to a pattern of transfers, they will choose not to compensate children in bad outcomes, as much as predicted by the standard (no uncertainty, no asymmetric information) dynastic model of the family. Alternatively, parents may choose to forgo any insurance, and offer a fixed level of bequest, to elicit greater effort from their children. The optimal transfers structure that the author derives, reconciles the predictions of the altruistic family model, with much of the existing evidence on inter-generational transfers, which suggests that parents compensate only partially, or not at all, for earnings differentials among their children. Moreover, the author shows that Ricardian equivalence holds in this setup, except when non-negativity constraints are binding.